Crisis and Recovery : Role of the Exchange Rate Regime in Emerging Market Countries - Tsangarides, Charalambos (Washington, D.C. : International Monetary Fund, 2010)
This paper examines the role of the exchange rate regime in explaining how emerging market economies fared in the recent global financial crisis, particularly in terms of output losses and growth resilience. After controlling for regime switches during the crisis, using alternative definitions for pegs, and taking account of other likely determinants, we find that the growth performance for pegs was not different from that of floats during the crisis. For the recovery period 2010-11, pegs appear to be faring worse, with growth recovering more slowly than floats. These results suggest an asymmetric effect of the regime during and recovering from the crisis. We also find that proxies of the trade and financial channels are important determinants of growth performance during the crisis, while only the trade channel appears important for the recovery thus far.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet